VD_FINDINFO Jug / 2012 / 337 vom 12. Juni 2012 - VD Tribunal cantonal (2012)
TORT MORAL, PARTIE CIVILE, FRAIS DE LA PROCÉDURE, DÉPENS | 47 CO, 49 CO, 308 CPC (CH), 320 CPC (CH), 135 CPP (CH), 138 CPP (CH), 398 al. 5 CPP (CH), 426 al. 4 CPP (CH)